"Crecimiento y fijación potencial de carbono en plantaciones forestales mixtas de araucaria hunsteinii. En La Zona Atlántica, Costa Rica." - Martínez-Albán, Victor (Instituto Tecnológico de Costa Rica, 2014)
It was performed a silvicultural assessment of growth and the capacity to fix atmospheric carbon in forest plantations of Araucaria hunsteinii in the Atlantic zone of Costa Rica. The main growth parameters were taken from the chronosequenced measurements in the different models of mixed forest plantations, besides taking composite soil samples to compare the levels of carbon fixation on it. For this evaluation were taken 6 models in the collection presented by Reforest the Tropics (RTT), where 4 are mixed plantations of A. hunsteinii, 1 is a monoculture plantation A. hunsteinii and the latest model is a mixture of 5 tropical species . These plantations indicated significant differences in diameter growth between them, where the best growth was presented by BySN, significant differences were also obtained on the growth presented by A. hunsteinii in 5 models where it is part of the plantation design. Chancho was the model with the most carbon dioxide fixation in biomass at the age of 10 years with 320,86 𝑚𝑔 ℎ𝑎. In the analysis done to soils of the forest plantations were obtained that there are significant differences when all the models and whiteness were compared, the main difference was presented by Yale with Coffee plantation, and the model with the most carbon in soil is Chancho with 256,59 𝑀𝑔 ℎ𝑎.
Proyecto de Graduación (Licenciatura en Ingeniería Forestal). Instituto Tecnológico de Costa Rica. Escuela de Ingeniería Forestal, 2014.
Keywords: Materia orgánica; Densidad; Biomasa; Trópico; Competencia